IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) MATA PELAJARAN PENDIDIKAN AGAMA ISLAM PADA SMK NEGERI 2 PENGASIH KULON PROG - Wardani, Wardani (Universitas Ahmad Dahlan, 2014)
This study aims to determine: 1) implementation of the Education Unit Level Curriculum (SBC) Subjects Islamic Education (PAI) at SMK Negeri 2 Compassionate, 2) the factors supporting and hindering implementation of SBC Subjects PAI in SMK Negeri 2 Compassionate. This research is a descriptive study using a qualitative analysis, in SMK Negeri 2 Compassionate Progo Regency for 1 month with the object of research is the implementation of SBC subjects of Islamic Education. The subjects of the study consisted of Principals and Vice-principals, teachers of Islam, the school committee, the Administrative Officer, Students of SMK Negeri 2 Compassionate. Data collected by in-depth interviews, observation documents. Data analysis was performed after testing the validity of data triangulation. Data analysis through the stages of editing, coding, data presentation, and conclusion. The results showed as follows. First, the implementation in the preparation phase of the syllabus and Learning Implementation Plan (RPP) has been good. During the implementation phase, the activity of students in pembeJajaran PAI in N 2 Compassionate pretty good, delivery of content is appropriate RPP, but the material can not be fully controlled by the student. In the evaluation phase, the average value obtained PAI N 2 Compassionate above the KKM is Class X, XI, XII, respectively 79.80, and 81 with KKM at 75. Second, the factors that support or hinder the implementation consists of factors students, factor learning atmosphere, facilities and infrastructure factors in the classroom or in the school, teachers factors and environmental factors. In conclusion, the implementation of the curriculum subjects PAI in N 2 Compassionate generally been going well. Factors that support or hinder the implementation of SBC is not always intrusive and do not always support due to various factors depend on the ability of teachers to manage classes.